2010
DOI: 10.3758/brm.42.1.118
|View full text |Cite
|
Sign up to set email alerts
|

SYLLABARIUM: An online application for deriving complete statistics for Basque and Spanish orthographic syllables

Abstract: For more than a decade, a large body of empirical evidence has shown that, for the recognition of a written word, subword units are accessed at early stages of visual word processing, and the properties of these subword units have an effect on reading behavior. Researchers have repeatedly reported data showing how letters and phonemes (e.g., Pelli, Farell, & Moore, 2003;Perea, Duñabeitia, & Carreiras, 2008b;Rastle & Brysbaert, 2006), syllables (e.g., Conrad, Stenneken, & Jacobs, 2006Perea & Carreiras, 1998), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 67 publications
(68 reference statements)
0
24
0
1
Order By: Relevance
“…ERPs were quantified by taking the mean amplitude of each participant and electrode in two temporal epochs corresponding to the two primary components of interest found to be sensitive to masked language switch cost ERP effects: the N250 (covering a time window between 180 and 260 ms post-target onset) and the N400 (represented by a time window between 350 and 500 ms). These two epochs of interest are in accordance with those reported in earlier studies on a similar topic using a parallel procedure (e.g., Chauncey et al, 2008Chauncey et al, , 2011Dunabeitia et al, 2010b;Holcomb and Grainger, 2006;Hoshino et al, 2010;Midgley et al, 2009b). These two epochs were analyzed separately in two sets of repeated measures analyses of variance (ANOVAs).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…ERPs were quantified by taking the mean amplitude of each participant and electrode in two temporal epochs corresponding to the two primary components of interest found to be sensitive to masked language switch cost ERP effects: the N250 (covering a time window between 180 and 260 ms post-target onset) and the N400 (represented by a time window between 350 and 500 ms). These two epochs of interest are in accordance with those reported in earlier studies on a similar topic using a parallel procedure (e.g., Chauncey et al, 2008Chauncey et al, , 2011Dunabeitia et al, 2010b;Holcomb and Grainger, 2006;Hoshino et al, 2010;Midgley et al, 2009b). These two epochs were analyzed separately in two sets of repeated measures analyses of variance (ANOVAs).…”
Section: Discussionmentioning
confidence: 95%
“…The masked priming languageswitching paradigm combined with Event-Related Potential (ERP) recording is an extremely valuable approach for researchers exploring the time-course of language identification. Using such approach, it has been shown that bilinguals can automatically and unconsciously detect the language of a word within 200 milliseconds of stimulus onset (Chauncey et al, 2008(Chauncey et al, , 2011Dunabeitia et al, 2010b). In masked priming ERP studies exploring language detection, participants are typically presented with primes for 50 ms (i.e., below the threshold of conscious recognition) and unrelated targets that are in the same or different languages (e.g., casa-DOG vs.…”
Section: Introductionmentioning
confidence: 99%
“…The most similar effort is the Syllabarium (Duñabeitia, Cholin, Corral, Perea, & Carreiras, 2010), which is a Webbased tool accessing a database containing information on word frequencies and syllable frequencies by token and syllable position. Standalone software packages are also available for Spanish and other languages that provide subsets of the properties in EsPal (Davis, 2005;Davis & Perea, 2005;New, Pallier, Brysbaert, & Ferrand, 2004;Perea et al, 2006).…”
mentioning
confidence: 99%
“…Besides, recent studies have also focused on Basque multilinguals in order to explore language-mediated domain-general cognitive processes such as attention (e.g., see Antón et al, 2014, 2016; Duñabeitia et al, 2014) or learning (e.g., Cenoz, 1998). Given this increased presence of studies with Basque multilinguals, some efforts have been made to provide researchers with databases that allow for the creation of adequately characterized research materials (e.g., Perea et al, 2006; Duñabeitia et al, 2010a; Acha et al, 2014). …”
Section: Introductionmentioning
confidence: 99%